Avifauna evaluation of the La Paz City, Bolivia - Martínez, Omar (2010)
Since 1996 to 2003, we realized an inventory and obtained data on the natural history, trophic guilds and mi- gration patterns of the avifauna of La Paz (Bolivia), based on direct observation, random walks and captures with mist nets. A total of 136 species of birds in 30 localities of study were registered. Tyrannids, Emberizids and Furnariids were the families most representatives with 19, 16 and 15 species, respectively. Eighteen species of waterbirds and two species of passerine rush (called totorales) specialists as Tachuris rubigastra and Phleocryptes melanops, were registered. Two furnariids species (Cranioleuca henricae and Upucerthia harterti) were Bolivian endemics. We detected 57 species in some category of migrants. Unusual elevational movements were observed for five species (e.g. Pitangus sulphuratus, Pyrocephalus rubinus). Nineteen spe- cies were considered rare (e.g. Lesbia nuna, Poospiza boliviana). Insectivores and frugi-granivores were the trophic guilds most representatives between communities. The La Paz City Valley is one obligatory route for many latitudinal (neartic and austral) and altitudinal migrants birds, which arise from highland by the western and species of mountain forest (called Yungas) by the eastern.